EmoTrack headset and smart application: An integrated solution for emotional regulation and mental health support in Indonesia’s 5.0 modernization era - Nafisya, Siti Naila (Public Health Risk Assesment Journal, 2025)
Background: Mental health issues are increasingly prevalent in Indonesia, with limited resources, social stigma, and insufficient community awareness posing barriers to effective management. Methods: This study introduces the EmoTrack Headset-App, a novel, integrated self-therapy device combining transcranial direct current stimulation (tDCS) and binaural beat technology to support mental health and emotional regulation. This solution enables real-time mental health monitoring and offers tailored interventions through a wearable headset linked to a smartphone application. Data collection involved a literature review and device prototyping to assess the feasibility and potential impact of EmoTrack. Findings: Results indicate that tDCS and binaural beats enhance emotional stability and reduce symptoms of anxiety and depression. Additionally, the app's community feature facilitates user engagement, helping to destigmatize mental health issues and encouraging shared experiences. Conclusions: The EmoTrack system has the potential to revolutionize mental health care by improving access to preventive and therapeutic support in Indonesia. Novelty/Originality of this article: This innovation uniquely combines tDCS and binaural beats within a single device, presenting a pioneering tool that addresses mental health and emotional regulation in a wearable, user-friendly format.